Investigation a new technique of automatic variable key using two dimensional matrix approach to achieve perfect security. (2018) - Das, Moumita; Roy, Pranab; Goswami, Rajat Subhra; Bhunia, Chandan Tilak
In all cryptosystem, the major challenge is to make the key unbreakable. Shannon proposed that, key would be impossible to break if the key is made time variant. The variable keys are highly enforced to provide the perfect security in automatic variable key which is more novel approaches in information security field. The time variant key can be implemented by changing keys from session to session during data transfer for achieving perfect security. To attain this goal, key should be made variable by an agreement that creates new key for each session of data transfer at both sender and receiver sides. In this paper, we have proposed a new technique to generate time variant key by enhancing the randomness between two successive keys. The main purpose of this technique is to produce numerous keys in symmetric key cryptosystem with a behaviour which will be difficult to guess by the attacker.